A comparison of stratospheric photochemical response to different reconstructions of solar ultraviolet radiative variability. (September 2015) - Bolduc, Cassandra; Bourqui, Michel S.; Charbonneau, Paul
Abstract: We present calculations of stratospheric chemical abundances variations between different levels of solar activity using a simple photochemistry model in transient chemistry mode. Different models for the reconstruction of the solar spectrum, as well as observations from the SOLar STellar Irradiance Comparison Experiment (SOLSTICE) and Spectral Irradiance Monitor (SIM) on the SOlar Radiation and Climate Experiment (SORCE) satellite, are used as inputs to the calculations. We put the emphasis on the MOnte CArlo Spectral Solar Irradiance Model (MOCASSIM) reconstructions, which cover the spectral interval from 150 to 400 nm and extend from 1610 to present. We compare our results with those obtained with the Naval Research Laboratory Solar Spectral Irradiance (NRLSSI) model as well as with the Magnesium-Neutron Monitor (MGNM) model over a period of time spanning the ascending phase of Cycle 22. We also perform the calculations using SORCE composite spectra for the descending phase of Cycle 23 and with the reconstructed MOCASSIM, NRLSSI and MGNM spectra for the same period for comparison. Finally, we compare the chemical abundances obtained for the Maunder Minimum with those obtained for the Cycle 23 minimum (in March 2009) and find that stratospheric ozone concentration was slightly higher during the recent minimum, consequent to the small positive variability between the MOCASSIM spectra for both epochs, especially below 260 nm. We find that the response in stratospheric ozone is not only dependent on the variability amplitude in the solar spectrum (especially in the 200–240 nm band), but also significantly on the base level of the minimum solar spectrum. Abstract : Highlights: We run simulations of stratospheric chemistry in pure photochemistry mode. We use different solar spectra as inputs representing minimum and maximum activity. The spectra are produced by 3 models (in agreement within 5%) and observations. Ozone variability during the solar cycle is very sensitive to the spectral details.